DOP01 Extracellular Nicotinamide Phosphoribosyltransferase (eNAMPT): possible new target and biomarker in inflammatory bowel diseases. (25th January 2019) - Colombo, G; Travelli, C; Porta, C; Stocco, G; Malavasi, F; Genazzani, A A
Abstract: Background: Nicotinamide phosphoribosyltransferase (NAMPT) is a pleiotropic enzyme involved in cellular mammalian metabolism. It is present in two different forms: an intracellular form, called iNAMPT, which acts as an enzyme-producing nicotinamide mononucleotide, precursor of NAD (Chiarugi et al., 2012), and an extracellular form, eNAMPT. eNAMPT is a metabokine with with paracrine and autocrine effects on different cell types (e.g. immune and cancer cells). However, the mechanism of action is still unknown, only recently TLR4 as been proposed as the possible eNAMPT receptor. eNAMPT levels are increased in inflammatory bowel diseases (IBD). It has been reported that serum eNAMPT levels correlate with the stage of the pathology: in an active state of the disease the level of eNAMPT are very high, however its levels are partially reduced in a remission stage. After 3 months of treatment, eNAMPT levels seem to be lowered, regardless of treatment class (Moschen et al., 2007). Abundant inflammatory stimuli are able to cause eNAMPT over-secretion, especially from innate immune cells. Methods: We investigated the role of eNAMPT in murine IBD models (DNBS and DSS models) and its neutralisation through a neutralising monoclonal antibody generated by us (C269). We took into account phenotypic effect as weight loss and colon shortening, but also the reduction of inflammatory genes with RT-PCR, tissue damage with H&E and IHC analysis, reduction of eNAMPT levels and lamina propria immune cells through FACS analysis. Therefore, we determined serum eNAMPT levels in a cohort of 21 paediatric IBD patients, upon infliximab treatment. Results: Exogenous administration of recombinant eNAMPT (i.p. 50 μg/mice) in DNBS model determined a worsening of IBD symptoms (increased weight loss, colon shortening and tissue damage). These symptoms are reduced after the treatment with an anti-eNAMPT monoclonal antibody (50 μg/mice/twice), also observable in a reduction of tissue damage through H&E analysis, in mRNA proinflammatory gene expression, especially IFNγ and its associated genes (e.g. IL12p40, IL23p19, IL18, IL22, and TBX21), usually up-regulated in IBD. Moreover, we observed a reduction in myeloid and T cells counterpart, through FACS analysis. Anti-eNAMPT antibody also determined a decrease of serum eNAMPT levels in DNBS model. Moreover, we performed ELISA analysis on sera of paediatric IBD patients, treated with infliximab. Responsive patients verified a reduction of initial high eNAMPT levels, while no-responsive maintained higher levels. Conclusions: We evaluated the role of eNAMPT in IBD and its possible neutralisation as a novel therapeutic strategy, through a monoclonal antibody. eNAMPT could be considered a biomarker upon infliximab response.